If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2r + 6 + -12r = 0 Reorder the terms: 5 + 6 + -2r + -12r = 0 Combine like terms: 5 + 6 = 11 11 + -2r + -12r = 0 Combine like terms: -2r + -12r = -14r 11 + -14r = 0 Solving 11 + -14r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -14r = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -14r = 0 + -11 -14r = 0 + -11 Combine like terms: 0 + -11 = -11 -14r = -11 Divide each side by '-14'. r = 0.7857142857 Simplifying r = 0.7857142857
| x+3(2)=7 | | 14r^2-r^2= | | 5a+26=6 | | -7(5x+8)=-196 | | 5m-17=-18 | | -3+53.8=-1.2 | | -6(4x-9)=6 | | 6(7x-5)=96 | | 1.08+n=15.74 | | -13.42=49.87-0.3p | | 36=-3(22-y)+3(y-2) | | 5-2r+2+12r= | | .25(x+3)=.5x+3 | | -0.8=-0.72 | | x+52=134 | | 3s-2=4s-14 | | 7(-6-2x)=-98 | | 14a+12= | | (4x-9)/(2x-3) | | 3m+8-m=48 | | X^3-x^3=0 | | F(x)=6/7x | | 3x/8-8=4 | | 3x/8-8 | | 8(x-4)=12(x+1) | | 7m-2m+10=35 | | 0.72x+3.24x+32.58=89x-0.55x | | 2.75/0.08 | | 4x+5-3x=8+2x-6 | | -2x-48=4x+72 | | 7+2x=5x-31 | | -2x-4=4x+72 |